Management and 30-Day Mortality of Acute Coronary Syndrome in a Resource-Limited Setting: Insight From Ethiopia. A Prospective Cohort Study - Fanta, Korinan; Daba, Fekede Bekele; Asefa, Elsah Tegene; Melaku, Tsegaye; Chelkeba, Legese; Fekadu, Ginenus; Gudina, Esayas Kebede (Frontiers in Cardiovascular Medicine, 2021)
Background: Despite the fact that the burden, risk factors, and clinical characteristics of acute coronary syndrome (ACS) have been studied widely in developed countries, limited data are available from sub-Saharan Africa. Therefore, this study aimed at evaluating the clinical characteristics, treatment, and 30-day mortality of patients with ACS admitted to tertiary hospitals in Ethiopia. Methods: A total of 181 ACS patients admitted to tertiary care hospitals in Ethiopia were enrolled from March 15 to November 15, 2018. The clinical characteristics, management, and 30-day mortality were evaluated by ACS subtype. The Cox proportional hazards model was used to determine the predictors of 30-day all-cause mortality. A p-value < 0.05 was considered statistically significant. Results: The majority (61%) of ACS patients were admitted with ST-segment elevation myocardial infarction (STEMI). The mean age was 56 years, with male predominance (62.4%). More than two-thirds (67.4%) of patients presented to hospital after 12 h of symptom onset. Dyslipidemia (48%) and hypertension (44%) were the most common risk factors identified. In-hospital dual antiplatelet and statin use was high (>90%), followed by beta-blockers (81%) and angiotensin-converting enzyme inhibitors (ACEIs; 72%). Late reperfusion with percutaneous coronary intervention (PCI) was done for only 13 (7.2%), and none of the patients received early reperfusion therapy. The 30-day all-cause mortality rate was 25.4%. On multivariate Cox proportional hazards model analysis, older age [hazard ratio (HR) = 1.03, 95% CI = 1.003–1.057], systolic blood pressure (HR = 0.99, 95% CI = 0.975–1.000), serum creatinine (HR = 1.32, 95% CI = 1.056–1.643), Killip class > II (HR = 4.62, 95% CI = 2.502–8.523), ejection fraction <40% (HR = 2.75, 95% CI = 1.463–5.162), and STEMI (HR = 2.72, 95% CI = 1.006–4.261) were independent predictors of 30-day mortality. Conclusions: The 30-day all-cause mortality rate was unacceptably high, which implies an urgent need to establish a nationwide program to reduce pre-hospital delay, promoting the use of guideline-directed medications, and increasing access to reperfusion therapy.